COMPARISON OF OPPORTUNITIES FROM TWO THERAPEUTICAL COMPLEXES FOR CORRECTION OF VASCULAR HEMOSTASIS IN HYPERTENSIVES WITH METABOLIC SYNDROME - S. Yu. Zavalishina; I. N. Medvedev (Кардиоваскулярная терапия и профилактика)
Though there is a progress in medical science and practice, hypertension remains widely prevalent in economically developed countries, and is comorbid with metabolic syndrome. This leads to weakening of vascular wall functioning in these patients and developing conditions for the formation of intravascular thrombi of various location.Aim. Comparative assessment of hemostatic function correction of vessel wall in hypertensives with metabolic syndrome (MS) with the complex of valsartan and losartan together with metformin and nonmedication treatments.Material and methods. Under follow-up, there were 47 hypertensives, of 1-2 grade, risk 4, middle age. Controls were 25 healthy persons of the same age. The assessment of biochemical and hematological parameters was performed. For blood pressure correction, 24 patients were prescribed valsartan 160 mg daily, 23 patients — losartan 100 mg daily. For metabolism optimization all patients were prescribed metformin 500 mg b.i.d., hypocaloric diet and regular physical activity of tolerable intensity.Results. The application of a complex with valsartan leads to normalization in hypertensives with MS the function of vascular wall in 4 months. Further non-strict adherence to the prescribed nonmedication part of the complex retains positive effect by the end of follow-up (12 months). Usage of losartan improves, but does not normalize vessel wall function in 4 months. Further non-strict adherence of non-medication part of treatment, regardless the continuation of losartan and metformin intake, decreases the achieved effect of treatment.Conclusion. Usage of treatment complex of hypocaloric diet, physical exercise and metformin helps to influence positively vascular hemostasis in hypertensives with MS in case of valsartan inclusion, and is less effective if replaced by losartan.